2014
DOI: 10.1164/rccm.201311-1986oc
|View full text |Cite
|
Sign up to set email alerts
|

miR-31 Dysregulation in Cystic Fibrosis Airways Contributes to Increased Pulmonary Cathepsin S Production

Abstract: Rationale: Cathepsin S (CTSS) activity is increased in bronchoalveolar lavage (BAL) fluid from patients with cystic fibrosis (CF). This activity contributes to lung inflammation via degradation of antimicrobial proteins, such as lactoferrin and members of the b-defensin family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 54 publications
1
82
1
1
Order By: Relevance
“…Interestingly, a recent study by Weldon et al (2014), has revealed a new mechanism through which cathepsin S expression becomes elevated in CF BAL fluid of nonPseudomonas aeruginosa infected patients. Epithelial cells were found to drive expression of the protease in an IRF-1 dependent manner that was a result of the loss of miR-31 which negatively regulates the expression of this transcription factor (Weldon et al, 2014).…”
Section: Cystic Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study by Weldon et al (2014), has revealed a new mechanism through which cathepsin S expression becomes elevated in CF BAL fluid of nonPseudomonas aeruginosa infected patients. Epithelial cells were found to drive expression of the protease in an IRF-1 dependent manner that was a result of the loss of miR-31 which negatively regulates the expression of this transcription factor (Weldon et al, 2014).…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Epithelial cells were found to drive expression of the protease in an IRF-1 dependent manner that was a result of the loss of miR-31 which negatively regulates the expression of this transcription factor (Weldon et al, 2014).…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…IRF1 is frequently part of TLR signalling as it can be activated directly downstream from TLR2 [54]. However, in this study, cathepsin S transcription was not found to be dependent on P. aeruginosa infection [53]. Although not further investigated in this study, TLR2 activation and subsequent cathepsin S transcription by IRF1 could still potentially exist through infection by Staphylococcus aureus , a potent trigger of TLR2 signalling and a common resident pathogen in CF lungs [54].…”
Section: Mirnas Cf and Tlrsmentioning
confidence: 94%
“…Weldon et al [53 ]found a significant increase of cathepsin S in the bronchoaveolar lavage fluid of CF patients over that from non-CF lungs. Together with neutrophil elastase, this potent protease and pro-inflammatory mediator is thought to be an important exacerbator of lung tissue destruction and inflammation.…”
Section: Mirnas Cf and Tlrsmentioning
confidence: 99%
“…For example, during influenza A infection, upregulation of miR-136 promotes IFN-β accumulation in an A549 epithelial cell model, promoting viral killing [35] . In response to bacteria such as Mycobacterium bovis , Staphylococcus aureus , or Pseudomonas aeruginosa altered expression of miR-21, miR-124, and miR-93 regulates production of inflammatory cytokines, such as IL-8, by the epithelium [36][37][38] .…”
Section: Epitheliummentioning
confidence: 99%